Full-scale resistance prediction in finite waters: A study using computational fluid dynamics simulations, model test experiments and sea trial measurements. (February 2017) - Haase, Max; Davidson, Gary; Binns, Jonathan; Thomas, Giles; Bose, Neil
The development of large medium-speed catamarans aims increasing economic viability and reducing the possible negative influence on the environment of fast sea transportation. These vessels are likely to operate at hump speed where wave-making can be the dominating component of the total resistance. Shallow water may considerably amplify the wave-making and hence the overall drag force. Computational fluid dynamics is used to predict the drag force of medium-speed catamarans at model and full scale in infinite and restricted water to study the impact on the resistance. Steady and unsteady shallow-water effects that occur in model testing or full-scale operation are taken into account using computational fluid dynamics as they are inherently included in the mathematical formulations. Unsteady effects in the ship-model response were recorded in model test experiments, computational fluid dynamics simulations and full-scale measurements and found to agree with each other. For a medium-speed catamaran in water that is restricted in width and depth, it was found that computational fluid dynamics is capable of accurately predicting the drag with a maximum deviation of no more than 6% when compared to experimental results in model scale. The influences of restricted depth and width were studied using computational fluid dynamics where steady finite width effects in shallow water and finite depth effects at finite width were quantified. Full-scale drag from computational fluid dynamics predictions in shallow water ( h/L = 0.12 – 0.17) was found to be between full-scale measurements and extrapolated model test results. Finally, it is shown that current extrapolation procedures for shallow-water model tests over-estimate residuary resistance by up to 12% and underestimate frictional forces by up to 35% when compared to validated computational fluid dynamics results. This study concludes that computational fluid dynamics is a versatile tool to predict the full-scale ship resistance to a more accurate extent than extrapolation model test data and can also be utilised to estimate model sizes that keep finite-water effects to an agreed minimum.